Activity levels and return to work following total knee arthroplasty in patients under 65 years of age. (August 2017) - Scott, C. E. H.; Turnbull, G. S.; MacDonald, D.; Breusch, S. J.
Abstract : Aims: Little is known about employment following total knee arthroplasty (TKA). This study aims to identify factors which predict return to work following TKA in patients of working age in the United Kingdom. Patients & Methods: We prospectively assessed 289 patients (289 TKAs) aged ≤ 65 years who underwent TKA between 2010 and 2013. There were 148 women. The following were recorded pre-operatively: age, gender, body mass index, social deprivation, comorbidities, indication for surgery, work status and nature of employment, activity level as assessed by the University of California, Los Angeles (UCLA) activity score and Oxford Knee Score (OKS). The intention of patients to return to work or to retire was not assessed pre-operatively. At a mean of 3.4 years (2 to 4) post-operatively, the return to work status, OKS, the EuroQol-5 dimensions (EQ-5D) score, UCLA activity score and Work, Osteoarthritis and joint-Replacement (WORQ) score were obtained. Univariate and multivariate analyses were performed. Results: Of 261 patients (90%) who were working before TKA, 105 (40%) returned to any job, including 89 (34%) who returned to the same job at a mean of 13.5 weeks (2 to 104) post-operatively. A total of 108 (41%) retired following TKA and 18 remained on welfare. Patients not working before the operation did not return to work. Median UCLA scores improved in 125 patients (58%) from 4 (mild activity) to 6 (moderate activity) (p < 0.001). Significant (p < 0.05) factors which were predictive of return to any work included age, heavy or moderate manual work, better post-operative UCLA, OKS and EQ-5D general health scores. Significant predictive factors of return to the same work included age, heavy or moderate manual work and post-operative OKS. Multivariate analysis confirmed heavy or moderate manual work and age to independently predict a return to either any or the same work. All patients aged < 50 years who were working pre-operatively returned to any work as did 60% of those aged between 50 and 54 years, 50% of those aged between 55 and 59 years and 24% those aged between 60 and 65 years. Conclusion: If working pre-operatively, patients aged < 50 years invariably returned to work following TKA, but only half of those aged between 50 to 60 years returned. High post-operative activity levels and patient reported outcome measures do not predict return to work following TKA. Cite this article: Bone Joint J 2017;99-B:1037–46.